2018
DOI: 10.3389/fphar.2018.00629
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Arrest and Apoptosis in HT-29 Cells Induced by Dichloromethane Fraction From Toddalia asiatica (L.) Lam.

Abstract: The roots of Toddalia asiatica (L.) Lam. (TA) has been often used in Chinese folk medicine to treat different diseases, including but not limited to arthritis, injuries, stomachache, and even tumors. However, the anti-cancer effects and the action mechanisms of TA remain elusive. Therefore, we firstly evaluated the effects of different extracts of TA on the growth of human colon cancer cells, and then tried to further elucidate their underlying molecular mechanisms. As a result, the dichloromethane fraction (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…When cells undergo apoptotic change due to cell membrane damage, PS translocate from the inner leaflet of the plasma membrane to the outer leaflet, which is considered as an early event in apoptosis. 27 In the present study, we found that S. cumini-induced apoptosis in OSCC cells through the induction of phosphatidylserine externalization and these morphological changes related to apoptosis further substantiate our dual staining investigation.…”
Section: Discussionsupporting
confidence: 87%
“…When cells undergo apoptotic change due to cell membrane damage, PS translocate from the inner leaflet of the plasma membrane to the outer leaflet, which is considered as an early event in apoptosis. 27 In the present study, we found that S. cumini-induced apoptosis in OSCC cells through the induction of phosphatidylserine externalization and these morphological changes related to apoptosis further substantiate our dual staining investigation.…”
Section: Discussionsupporting
confidence: 87%
“…Treating HT-29 human colon cancer cell line with this plant product promoted both intrinsic and extrinsic pathways of apoptosis by enhancing the activity of caspases -8, -9, and -3. Moreover, ROS generation appears to be the main reason for the cell cycle arrest in these cells following extract exposure [ 66 ]. Ethanolic extract of the rhizome of Cyperus rotundus (known as coco-grass, Java grass, nutgrass, purple nutsedge or purple nutsedge, red nut sedge, Khmer kravanh chruk) suppresses the proliferation of triple-negative human breast cancer cell line, MDA-MB-231.…”
Section: Major Apoptotic Pathwaysmentioning
confidence: 99%
“…T. asiatica has played a very important role in traditional medicine, and the whole plant can be used as medicine, especially its root often used in the folk ( Yang et al, 2013 , Li et al, 2018 ). The studies of chemical composition showed that the main chemical components were alkaloids and coumarins in T. asiatica ( Wang et al, 2009 , Hu et al, 2014 , Sukieum et al, 2018 , Lin and Chen, 2020 ).…”
Section: Introductionmentioning
confidence: 99%